Interculturality Beyond Migrant Literature (KULT_online, 2010)
In Toleranz und Konflikt. Interkulturelle Dimensionen der deutschsprachigen Gegenwartsliteratur (Tolerance and Conflict: Intercultural Dimensions of Contemporary German Literature) Georgeta Vancea demonstrates that interculturality is not unique to migrant literature but that this subject, in a latent manner, also characterises many works of native German authors. Despite its apparent weaknesses — like the vague concept of 'contemporary literature', or the careless handling of both primary and secondary literature — the study shows how German-speaking writers deal with current phenomena such as migration, multiculturality, foreignness and xenophobia. It follows from the analysis that many contemporary works in German propagate a border-crossing ethic of tolerance whose origins lie in the Enlightenment but whose potential also arises from the heritage of grave German history.